A study of radon-222 levels in foamed light concrete - Syahrul Affandi Saidi; Mohamad Suhaimi Jaafar; Mohammad Khairul Azhar Abdul Razab; Nik Noriman Zulkepli (2013)
The purpose of this study is to measure and monitor the radon concentration in a fabricated foamed light concrete. Various proportions of Portland cement, mine sand, water and foamed were used in fabricating foamed light concrete. The concentration of radon released from the fabricated concrete was measured using Radon Monitor Model 05-420 from the Honeywell Inc. U.S.A. Results of this research showed that the mean radon concentration in foamed light concrete was 1.9pCi/L. The current radon concentration was proportional to temperature and inversely proportional to humidity. Gradual increased of radon concentrations were detected after three days of measurements, indicating a build up of airborne Rn due to Rn emanations from the fabricated foamed light concrete. However,with proper ventilations, the accumulation of the Rn emanated can be further reduced below the measured level. From this research finding, the fabricated foamed light concrete can beutilized as one of the alternatives to reduce radon concentration levels in human environment